Analisis Penyebab Over Heating Untuk Tindakan Perawatan Pada Screw Compressor Di PT. Semen Padang Unit Indarung IV - Candra, Adi; Abu, Risal; Mukhnizar, Mukhnizar; Zulkarnain, Zulkarnain; Azman, Azmil (Jurnal Teknik Industri Terintegrasi (JUTIN), 2023)
Semen Padang Indarung IV unit has a screw compressor type compressor unit to produce high pressure air. In its operations, one of the Atlas Copco type compressor units often experiences over heating problems, namely the working temperature exceeds 1000 C. The method used is trouble shooting the compressor system, such as checking the lubricating oil, pressure, valves, working temperature and cooling system. , as well as overhaul maintenance actions if necessary. Based on the research results, it was found that the factors that cause overheating of the compressor are: Dirty air quality affects the condition of the air filter for air supply, limited space for placing the compressor causes the air supply to decrease, the oil filter has passed its useful life and is not suitable for use, and the oil cooler is clogged with scale, which hinders the oil cooling process. Based on this damage, recommendations for maintenance activities on the Atlas Copco Compressor are: maintaining air quality, periodically cleaning the tubes in the oil cooler, replacing the new oil filter according to compressor specifications, as well as comprehensive maintenance measures